Pishnahad va tarh-i ta`sisi : (Kumisiyun-i Tadarukat va Dabirkhanah-'i Muvaqqat-i Jibhah-yi Hakimiyat-i Milli-yi Iran)
The recommendations and plan for the establishment of the National Sovereignty Front of Iran.